The role of Panax notoginseng saponins in cerebrovascular neurological disorders: an overview of mechanisms and functions - Wang, Bin; Gao, Xu; Zhang, Yali; Xiao, Yuhua; Chen, Tong; Shi, Zhouying; Yuan, Yue; Li, Ping (Frontiers in Pharmacology, 2025)
Cerebrovascular neurological disorders, especially high-mortality and disabling stroke subtypes such as ischemic stroke and hemorrhagic stroke, have become a major global health issue. In addition to conventional treatments, the role of herbal medicines and their active ingredients in the prevention and treatment of cerebrovascular and nervous system diseases has received increasing attention in recent years. Among them, the primary active ingredient of Panax notoginseng is Panax Notoginseng Saponins (PNS), has become a research hotspot due to its diverse pharmacological activities. Existing evidence suggests that PNS exhibits various effects including anti-inflammatory, antioxidant, anti-apoptotic, immune regulation, neuroprotection, blood sugar and lipid lowering, and cardiovascular protection. This review systematically searches multiple databases for literature related to PNS and cerebrovascular neurological disorders, focusing on summarizing the role of PNS in specific diseases such as ischemic stroke, hemorrhagic stroke, and neurodegenerative disorders, exploring its pharmacokinetic characteristics, main mechanisms of action, and clinical application prospects, aiming to provide a theoretical basis for the in-depth research and development of PNS in cerebrovascular neurological disorders.